The Nigerian Chronicle – November, 1910 - Johnson, Chris (Editor) (Nigerian Chronicle Office, Kumolu House, Shitta Street, Lagos, Southern Nigeria., 1910)
A weekly review of progress in politics, economics, commerce, and of general news, especially as affecting the Nigerians.
Keywords: Newspaper; Southern Nigeria